Assessment of Cross-Country Differences in Life Satisfaction and Quality of Life among Older Adults in Six EU Countries - Justyna KUJAWSKA (Communications of International Proceedings, 2025)
The aim of this article is to provide a comparative assessment of life satisfaction and key quality-of-life indicators among older adults in six European Union countries: Czechia, Germany, Lithuania, Poland, Spain and Sweden. Using data from the Survey of Health, Ageing and Retirement in Europe (SHARE, Wave 8; 2019–2020), complemented by macroeconomic indicators, the study examines how pension expenditure and the gender pension gap relate to self-rated health, the frequency and extent of social contacts (including social network size), and overall life satisfaction. By combining subjective and objective indicators, the analysis reflects the multidimensional nature of quality of life in later life. The findings reveal clear discrepancies between objective living conditions and reported life satisfaction. Countries characterised by high pension expenditure and well-developed social services — notably Sweden and Germany — display relatively high levels of life satisfaction despite only moderate outcomes in self-rated health and social contact frequency. By contrast, Poland and Spain, despite comparable levels of self-rated health and similar intensity of social contacts, report lower life satisfaction, suggesting a stronger influence of institutional stability, perceived security and culturally shaped expectations. Lithuania and Czechia — countries with lower income levels and poorer health indicators — nonetheless demonstrate higher life satisfaction than Poland and Spain, indicating that life satisfaction cannot be explained solely by material or structural conditions. Overall, the study highlights the importance of public policies that account not only for economic and health-related factors but also for institutional stability, the quality of public services, levels of social trust and the alignment of pension systems with citizens’ expectations. These findings underline that subjective evaluations of quality of life in older age are shaped by a complex interplay of structural conditions, social relationships and cultural response patterns.
Keywords: quality of life of older adults; life satisfaction; self-rated health; material conditions; social relations.